The prohibited aspects in conventional bank contract according shariah principles / Muhammad Fikri Rosman - Rosman, Muhammad Fikri (2019)
Conventional Bank is a bank that conducts conventional business activities which in its activities provide services in payment traffic. but there are aspects that are prohibited in this conventional bank such as riba gharar maysir and so on. This study focuses specifically on the three things that are commonly used, riba gharar and maysir. The purpose of this research is the prohibited aspects in conventional bank contract according to shariah principle. The problem statement is to understand the concept of Islamic banking such as mudhrabah, ijarah and so on. Prohibited aspects in bank contract such as car loan and house loan were also discussed in this study to identify the problems faced and solutions. The improvement measures undertaken by Public Bank. The research has used data collection methods through interviews and observations on Public Bank where an interview session was made with two respondents to obtain accurate information about the Public Bank product. The findings show that there is a element of riba and Gharar in the car loan and house loan.